Optimization of the fermentation process and antioxidant activity of mixed lactic acid bacteria for honeysuckle beverage - Ran, Junjian; Tang, Yuhan; Mao, Weize; Meng, Xia; Jiao, Lingxia; Li, Yongchao; Zhao, Ruixiang; Zhou, Haoyu (Frontiers in Microbiology, 2024)
The aim of the research was to obtain a high health care honeysuckle beverage with strong antioxidant activity. Honeysuckle (Lonicera japonica Thunb) was used as the raw material in this experiment. The effects of fermentation temperature, fermentation time, lactic acid bacteria inoculation amount and sugar addition amount on the sensory quality of honeysuckle beverage were investigated by single factor test and orthogonal test, and the best process was obtained. The physicochemical indexes and antioxidant activity of honeysuckle beverages fermented with lactic acid bacteria were studied. The results showed that the fermentation temperature of the beverage was 37 °C, the fermentation time was 24 h, the inoculation amount of Lactiplantibacillus plantarum and Lactobacillus acidophilus mixed starter (1:1) was 3%, and 8% white granulated sugar was added. The highest sensory score was 87.30 ± 0.17, which was the optimal process. The honeysuckle liquid mixed inoculation with Lactiplantibacillus plantarum and Lactobacillus acidophilus was fermented for 24 h. The number of viable bacteria reached 9.84 ± 0.02 lg cfu/mL, the pH value was 3.10 ± 0.01, and the total polyphenol content was 7.53 ± 0.03 mg GAE/g. The number of lactic acid bacteria, pH, total polyphenol content and free radical scavenging rate were significantly increased (P < 0.05) compared with the non-inoculated and single-inoculated lactic acid bacteria. To sum up, it was concluded that a better quality beverage could be obtained by fermenting a solution of honeysuckle with Lactiplantibacillus plantarum and Lactobacillus acidophilus mixed fermentation agent, providing a new approach and new ideas for the development of deep processing and fermented beverages using honeysuckle.